Biochemical and biological characterization of two serine proteinases from Colombian Crotalus durissus cumanensis snake venom (2013)
Two clotting serine proteinases, named Cdc SI and Cdc SII, were isolated and characterized for the first time from Colombian Crotalus durissus cumanensis snake venom. The enzymes were purified using two chromatographic steps: molecular exclusion on Sephacryl S-200 and RP-HPLC on C8 Column. The molecular masses of the proteins, determined by MALDI-TOF mass spectrometry, were 28,561.4 and 28,799.2 Da for Cdc SI and Cdc SII, respectively. The aim of the present study was to evaluate enzymatic, coagulant and toxic properties of the two enzymes. The serine proteinases hydrolyzed specific chromogenic substrate (BaPNA) and exhibited a Michaelis-Menten behavior. Cdc SI had Vmax of 0.038 ± 0.003 nmol/min and KM of 0.034 ± 0.017 mM, while Cdc SII displayed values of Vmax of 0.267 ± 0.011 nmol/min and KM of 0.145 ± 0.023 mM. N-terminal sequences were VIGGDEXNIN and VIGGDICNINEHNFLVALYE for Cdc SI and Cdc SII, respectively. Molecular masses, N-terminal sequences, inhibition assays, and enzymatic profile suggest that Cdc SI and Cdc SII belong to the family of snake venom thrombin-like enzymes. These serine proteinases differed in their clotting activity on human plasma, showing a minimum coagulant dose of 25 µg and 0.571 µg for Cdc SI and Cdc SII, respectively. Enzymes also showed coagulant activity on bovine fibrinogen and degraded chain a of this protein. Toxins lack hemorrhagic and myotoxic activities, but are capable to induce defibrin(ogen)ation, moderate edema, and an increase in vascular permeability. These serine proteinases may contribute indirectly to the local hemorrhage induced by metalloproteinases, by causing blood clotting disturbances, and might also contribute to cardiovascular alterations characteristic of patients envenomed by C. d. cumanensis in Colombia. © 2012 Elsevier Ltd.